Genome-wide analysis of horizontally acquired genes in the genus Mycobacterium. Issue 1 (December 2018) - Panda, Arup; Drancourt, Michel; Tuller, Tamir; Pontarotti, Pierre
Abstract Horizontal gene transfer (HGT) was attributed as a major driving force for the innovation and evolution of prokaryotic genomes. Previously, multiple research endeavors were undertaken to decipher HGT in different bacterial lineages. The genusMycobacterium houses some of the most deadly human pathogens; however, the impact of HGT inMycobacterium has never been addressed in a systematic way. Previous initiatives to explore the genomic imprints of HGTs inMycobacterium were focused on few selected species, specifically among the members ofMycobacterium tuberculosis complex. Considering the recent availability of a large number of genomes, the current study was initiated to decipher the probable events of HGTs among 109 completely sequencedMycobacterium species. Our comprehensive phylogenetic analysis with more than 9, 000 families ofMycobacterium proteins allowed us to list several instances of gene transfers spread across theMycobacterium phylogeny. Moreover, by examining the topology of gene phylogenies here, we identified the species most likely to donate and receive these genes and provided a detailed overview of the putative functions these genes may be involved in. Our study suggested that horizontally acquired foreign genes had played an enduring role in the evolution ofMycobacterium genomes and have contributed to their metabolic versatility and pathogenicity.